Eradicating Criminal Acts of Corruption through the Follow the Asset Approach: A Conceptual Analysis from a Criminal Law Perspective - Hutagalung, Argo Johnnes Parlinggoman; Suhaidi, Suhaidi (Civiliza Publishing, 2025)
Corruption is an extraordinary crime that has a broad impact on the national economy, governance, and public trust. Efforts to eradicate corruption have tended to focus on the perpetrator (follow the suspect), thus suboptimally recovering state financial losses. One emerging approach is